Structural behavior and Thermal Stress Response of Steel Members under Thermo-Environmental Loading for Polymer Reinforced Structural Systems - Mohammed, Kamal Ali; Mezher, Thaer Matlab (Journal of Research Updates in Polymer Science, 2026)
The structural behavior and thermally induced stresses of steel members play an important role in the safety, serviceability and long-term performance of civil engineering structures exposed to high temperatures and high humidity. Variations in stiffness, thermal deformation and stress redistribution directly affect the bearing capacity, deflection limit and durability of structural components, especially when polymer-based coatings and hybrid polymer-metal systems are used for environmental protection. In this study, a numerical investigation is performed to measure the thermomechanical response of commonly used structural steels (AISI 304, 316, 1020 and 1045) subjected to coupled thermal and humid conditions. Key structural parameters including elastic stiffness degradation, thermal deflection and thermal stress development are evaluated to support rational material selection and performance-based structural design. The results show that increasing temperature gives a significant increase in deflection for all steel grades due to a reduction in Young’s modulus, while the thermally induced stress decreases as a result of hardness softening. Carbon steels (1020 and 1045) exhibit low thermal deflection and high structural stiffness, while stainless steels (304 and 316) exhibit superior resistance to moisture-induced corrosion and environmental degradation, which is essential for durability-oriented structural applications. These findings highlight the inherent trade-off between structural stiffness, thermal compatibility and environmental resistance when choosing a steel substrate.